2013
DOI: 10.1111/jar.12032
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Institutional Violence in Offenders with Intellectual Disabilities: The Predictive Efficacy of theVRAGand theHCR‐20

Abstract: The HCR-20 and the VRAG have excellent predictive efficacy in offenders with an ID. A structured clinical judgement based on the HCR-20 was especially predictive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
5
32
0
Order By: Relevance
“…Fitzgerald et al . () found that twice as many people with ID in medium‐secure care engaged in violence over a 6‐month period compared with a control group of patients without ID (80 vs. 40%); similar results were reported by Dickens et al . () who found that 72.1% of the ID sample had engaged in aggression and/or self‐harm compared with 47.2% of patients in the mental health pathway.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Fitzgerald et al . () found that twice as many people with ID in medium‐secure care engaged in violence over a 6‐month period compared with a control group of patients without ID (80 vs. 40%); similar results were reported by Dickens et al . () who found that 72.1% of the ID sample had engaged in aggression and/or self‐harm compared with 47.2% of patients in the mental health pathway.…”
Section: Introductionsupporting
confidence: 80%
“…Like Fitzgerald et al . (), the overall predictive validity of the HCR‐20 total score did not significantly differ between the ID and comparison groups. However, there were significant differences in the performance of the C5 subscale and SJ.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations